Role-stress and mental health of government officers of Nepal - Rayamajhi, Kedar Bahadur (Journal of Advanced Academic Research, 2017)
Stress is the mental phenomenon; caused from the various environmental factors. The main aim of this study is to explore relationship between the role-stress and mental health of government officer working under the different ministries of Nepal. The study was conducted among the 284 government officers comprising level I to III. Standard structured questionnaires were used to measure the role-stress and mental health. The study found that there was no significant difference between position regarding the impact of organizational role stress on their mental and physical health. There was no significant difference found between the class I and III at P = 1.000 followed by class I and II at P = 1.000 and class III and class II at P = 1.000. Data shows that perception of mental and physical health has no different on the basis of their position and job roles. The study observed that there is relationship between the role-stress and mental health. If role stress increased then it negatively effect in mental health. Government employee reported the effect of role stress in their daily life but study has not found the serious effect of role stress in mental health of employees because of their practices of coping mechanism. So, there is need to explore their coping mechanism to manage the stress. Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 40-54